Mass transfer and substrate utilization in biofilm reactors - Muslu, Yilmaz (Wiley, 1993)
AbstractMass transfer within microbial films is described using Monod‐type biological kinetics in terms of properties of packing material and the feed solution. For this purpose, computer techniques have been developed for the numerical evaluation of the normalized biofilm mathematical model. A second‐order partial differential equation, describing the mechanisms of dispersion phenomena inside the liquid layer, was then solved to determine the mass transfer coefficient. The application of the theory to earlier experimental data has also been demonstrated.